Answer:
**********************868/14=62********************
Step-by-step explanation:
Given equation :−1/2 (x+2) + 112x = 3
We have -1/2 in front of parenthesis on left side .
It's better to remove fraction in an equation, in order make it easier to solve.
In order to remove 2 from denominator of 2, we need to multiply each and every term by 2.
Multiplying each term in the equation by 2, we get
2* −1/2(x+2) +2* 112x = 2*3.
On simplifying this step, we get
-1(x+2) +224x = 6.
Distributing -1 over (x+2), we get
-x -2 +224x = 6
Combining like terms on left side, -x+224x=223x
223x -2 = 6
Adding 2 on both sides, we get
223x -2+2 = 6+2
223x = 8
Dividing both sides by 223, we get
223x/223 = 8/223.
x= 8/223.
Answer: 207/4 or -51.75
Step-by-step explanation:
Answer: 0.71428 or 5:7 or 5/7
Step-by-step explanation: just divide on a calculator
Answer:
x = 8
Step-by-step explanation:
The explanation are the pictures. I hope I gave you the correct answer.